2019
DOI: 10.1177/0003065119868680
|View full text |Cite
|
Sign up to set email alerts
|

Is Emerging Adulthood a New Developmental Phase?

Abstract: In 2000, Jeffrey Arnett, a developmental research psychologist, proposed a new phase of development that he called “emerging adulthood.” He delineated developmental challenges centered on identity, role exploration, and subjective experience and linked his observations to changes in the demographics and culture of contemporary society. This proposal elicited an extraordinary response in the research community, but the reaction among psychoanalysts has been tepid at best: developmental phases have not been amen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 74 publications
(100 reference statements)
0
9
0
1
Order By: Relevance
“…During this phase, young adults often face multiple life transitions simultaneously and struggle between seeking independence from parental control and deferring to their parents for advice about important topics including health care. [9][10][11] As a result, parents may continue to play an important role in HPV vaccine decision-making among young adults. [12][13][14] Prior survey-based studies have shown that HPV vaccination among young adults is influenced by perceived benefits of vaccination, 15 recommendations from providers, 13,15,16 parents and social networks.…”
Section: Introductionmentioning
confidence: 99%
“…During this phase, young adults often face multiple life transitions simultaneously and struggle between seeking independence from parental control and deferring to their parents for advice about important topics including health care. [9][10][11] As a result, parents may continue to play an important role in HPV vaccine decision-making among young adults. [12][13][14] Prior survey-based studies have shown that HPV vaccination among young adults is influenced by perceived benefits of vaccination, 15 recommendations from providers, 13,15,16 parents and social networks.…”
Section: Introductionmentioning
confidence: 99%
“…Arnett saw these processes as not only identifying the zeitgeist of a given generation as it approaches maturity but insisted that the cohort he studied represented a new developmental phase that would be repeated in subsequent generations [ 49 ]. If this is so, learning how to help emerging adults actualise themselves and contribute to others at lower personal costs remains a crucial mission.…”
Section: Discussionmentioning
confidence: 99%
“…For a growing number of people in the United States, the developmental stage of emerging adulthood (ages 18-25) coincides with their "college experience" (Arnett, 2006;Schwartz, 2016). Emerging adulthood is often a time for identity exploration, characterized by an eagerness for new experiences and a high level of self-focus (Arnett, 2000(Arnett, , 2006Syed, 2016;Gilmore, 2019). One way that college students experiment with their newfound freedom is by engaging in transient, casual sexual relationships (Bogle 2008;Gilmore, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging adulthood is often a time for identity exploration, characterized by an eagerness for new experiences and a high level of self-focus (Arnett, 2000(Arnett, , 2006Syed, 2016;Gilmore, 2019). One way that college students experiment with their newfound freedom is by engaging in transient, casual sexual relationships (Bogle 2008;Gilmore, 2019). Previous findings indicate that up to three-quarters of undergraduates have had casual sex (Paul et al, 2000), with nearly one third having done so within the last year (Fielder et al, 2013).…”
Section: Introductionmentioning
confidence: 99%